ENT 530 Social Media Portfolio: SU.SU / Nurul Nabilla Azali - Azali, Nurul Nabilla (2021)
SU.SU is an online business that sell kurma milk by Farm Fresh. It was commenced on April 20, 2021, through registration at Go E-commerce website. Kurma milk that were sold by SU.SU consist of kurma milk of different packaging. From the date of its commencement, our Facebook page have grown substantially, gaining a lot of customers and attention from them. In addition, they have taken a liking to our product that is the Farm Fresh Susu Kurma. According to our customers’ reviews and feedbacks, our product is liked by many of them as it gave them the unique yet premium taste of milk. Therefore, kurma milk by Farm Fresh is considered as a good marketable product that suit all ages and can be further expanded to many different areas in the future. Thus, as SU.SU’s Facebook page continue to grow, we are able to improve our method of marketing, handling customers and also our method on competing healthily with competitors of similar products. As a summary, this report provides an evaluation of my social media portfolio. It includes the introduction of business, mission and vision, product details, and my marketing method that I use to sell and promote my product by using Facebook page. The elements of marketing included in my Facebook page are the URL of SU.SU’s Facebook page, the Facebook page itself, teaser posts, hard sell posts and also soft sell postsand at the end, this report is concluded in a conclusion section.